2002
DOI: 10.1080/00071660120103648
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-incubation storage conditions on hatchability, chick weight at hatch and hatching time in broiler breeders

Abstract: 1. Eggs were stored for two different times at varying temperatures. The effects on hatchability, chick weight at hatch and hatching time were examined in two broiler breeder lines from 33 to 58 weeks of age. 2. Short storage (1 to 3 d). Storage at 20 degrees C compared with 16.5 degrees C reduced hatchability of all eggs set. No effect was observed on hatchability of fertile eggs, hatching time or chick weight. 3. Long storage (9 to 11 d). Storage at 16.5 degrees C compared with 10 degrees C decreased both ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 35 publications
(68 reference statements)
2
20
0
Order By: Relevance
“…This difference was most likely caused by the concomitant increase in age of the parent stock. Effects of strain have been found on hatching time and neonatal live weight of broiler chicks (Ruiz and Lunam, 2002), in accordance with the results of the present experiment. Reis et al (1997) found no differences in live weight at hatch between the sexes, but male chicks tended to hatch on average 3 h later than females.…”
Section: Discussionsupporting
confidence: 95%
“…This difference was most likely caused by the concomitant increase in age of the parent stock. Effects of strain have been found on hatching time and neonatal live weight of broiler chicks (Ruiz and Lunam, 2002), in accordance with the results of the present experiment. Reis et al (1997) found no differences in live weight at hatch between the sexes, but male chicks tended to hatch on average 3 h later than females.…”
Section: Discussionsupporting
confidence: 95%
“…PEDROSO et al (2005) obtained similar results; these authors mentioned that as the age of breeders advanced, characteristics related to egg fertility and hatchability gradually improved. The effect of age of breeders on hatchability was observed also by RUIZ and LUNAM (2002) who wrote that fertilised eggs stored at higher temperatures showed a reduced hatchability of fertile eggs. SEKER et al (2005) found significant effects between pre-incubation storage and egg weight on hatching results of Japanese quail eggs.…”
Section: Introductionmentioning
confidence: 83%
“…It is very well known that longer ESD before incubation associated with lower chick quality and postnatal performance in broilers (Christensen et al, 2001 andRuiz and Lunam, 2002;Tona et al, 2003 and2004). The present experiment was conducted to evaluate the interaction between ESD and BTs.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the supply of hatching eggs, variable market demands for broiler chicks and hatchery capacity, eggs are stored for 3 to 18 days before incubation. But storage longer than 7 days adversely affects embryonic development by slowing embryo metabolism and growth (Christensen et al, 2001;Yalcin and Siegel, 2003;Fasenko, 2007) and chick weight at hatch (Reis et al, 1997;Ruiz and Lunam, 2002). Long-term egg storage also affects the postnatal growth (Tona et al, 2003), however the mechanisms behind have not been clearly understood.…”
Section: Introductionmentioning
confidence: 99%